The effectiveness of non-steroidal anti-inflammatory drugs in the treatment of chronic pelvic pain syndrome - Т. Г. Романенко; О. М. Суліменко (Publishing House TRILIST, 2018)
Evidence-based medicine is an approach to medical practice in which the decision on the appointment of therapeutic, diagnostic or preventive measures is based on the evidence of their effectiveness and safety. The aim of the study. Assessment of the effectiveness and safety of the use of NSAIDs in the treatment of chronic pelvic pain in women of reproductive age. Materials and methods. Under supervision, there were 101 women of reproductive age with chronic pelvic pain syndrome (CPPS) on the background of chronic inflammatory processes of the pelvic organs. Patients, depending on the received treatment, were randomly divided into two groups: Group I (n = 54) - complex antibiotic therapy was conducted in combination with antiplatelet agents, antihypoxants, analgesics; Group II (n = 47) - complex antibiotic (AB) therapy was performed in combination with antiplatelet agents, antihypoxants and NSAIDs (DICLOSAFE, diclofenac sodium 100 mg). The exclusion criterion was the presence of an endometriosis in a patient. When patients were included in the study and 6 months after the completion of the treatment, a questionnaire was conducted to determine the severity of the pain syndrome, psychological status and quality of life. Results. Positive dynamics of quantitative and qualitative characteristics of the pain syndrome, as well as dynamics of its intensity as a result of conservative treatment for 6 months in Group ІІ, was noted. Also, in Group ІІ, statistically significant data on the reduction of depression and personal anxiety are noted, in contrast to the indicators of Group I. The results of the questionnaire of patients in group II after treatment indicated improvement of all components of physical health. Statistically significant differences with the indicators of Group I were obtained on the scale of the effect of pain on daily activity. In addition, after treatment in the Group II, the patients showed statistically significant changes in mental health and all its components. Conclusion. Pathogenetically grounded use of NSAIDs (DICLOSAFE suppositories) in the complex treatment of patients with CPPS allows to achieve a significant improvement in quality of life indicators due to the correction of pain syndrome.